2019
DOI: 10.1016/j.chest.2018.10.009
|View full text |Cite
|
Sign up to set email alerts
|

Change in FEV1 and Feno Measurements as Predictors of Future Asthma Outcomes in Children

Abstract: BACKGROUND: Repeated measurements of spirometry and fractional exhaled nitric oxide (FENO) are recommended as part of the management of childhood asthma, but the evidence base for such recommendations is small. We tested the hypothesis that reducing spirometric indices or increasing FENO will predict poor future asthma outcomes.METHODS: A one-stage individual patient data meta-analysis used data from seven randomized controlled trials in which FENO was used to guide asthma treatment; spirometric indices were a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
49
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(54 citation statements)
references
References 23 publications
5
49
0
Order By: Relevance
“…As higher memory Treg cells represent chronic inflammation, naive cells have no memory of sensitization to specific antigens. 33,48,49 Children with better lung functions are less likely to have asthma, 50,51 and indeed, high naive Tregs suggest that these children had no chronic immune activation compared to children with allergic sensitization and atopic dermatitis. 33 However, we did not observe lower Treg-memory cells in children with better lung function.…”
Section: Previous Literature and Interpretationmentioning
confidence: 99%
“…As higher memory Treg cells represent chronic inflammation, naive cells have no memory of sensitization to specific antigens. 33,48,49 Children with better lung functions are less likely to have asthma, 50,51 and indeed, high naive Tregs suggest that these children had no chronic immune activation compared to children with allergic sensitization and atopic dermatitis. 33 However, we did not observe lower Treg-memory cells in children with better lung function.…”
Section: Previous Literature and Interpretationmentioning
confidence: 99%
“…Poor control and history of exacerbation are known risk factors of future exacerbation . Fielding et al have recently confirmed the link between altered lung function and poor asthma control and risk of exacerbation . Thus, improving the identification of patients at risk of exacerbations remains an urgent unmet need in childhood asthma …”
Section: Population Characteristics According To 1‐year Outcomesmentioning
confidence: 96%
“…[21][22][23][24][25][26][27] Participant details at baseline are presented in Table 1 and have also been described elsewhere. 18 The mean (SD) participant age was 12.6 (3.1) years and 58% of participants were male.…”
Section: Study Subjectsmentioning
confidence: 99%
“…Our group has pooled the data collected in more than 1000 participants in seven randomized controlled trials (RCTs) where F E NO was used to guide asthma treatment . This analysis found that a 50% increase in FeNO between baseline and 3 months was associated with 11% increase in odds for poor asthma control 6 months after baseline . We used individual patient data from the same database of seven RCTs to address the question “What is the variability in F E NO over 3 months among children with stable asthma?”.…”
Section: Introductionmentioning
confidence: 99%